A study of the relationship between UK consumers purchase intention and store brand food products -- Take Nottingham city consumers for example - Chen, Kaochun (2008)
Recently, store brands play an important role in retail grocery strategy. More and more retailers put their effort to develop and market new store brands because consumers have been accepting store brands. Therefore, store brands have gradually influenced consumers purchase behaviours in order to provide an in-depth investigation of consumers purchase intention in store brands, the study choose food products among many product categories because when consumers hear the store brand, they must connect to food products. The purpose of study is to understand whether the relationship between consumers purchase intention, products perception and socio-economic status have direct connections. Besides, the study use questionnaires to test consumers buying perception and choose participants by random, participants are from Nottingham city area. Total amount of the questionnaire is 110 copies, and 104 copies are validity. The ANOVA was used in analysing data. Furthermore, the study found age variable and education variable have no influence in consumers purchase intention. However, income and family size do influence consumers purchase intention. In terms of product perception, consumers think less risk and cheaper price can increase their purchase motivation, but value and quality variables are not decisive factors for them to buy the store brand food products in superstores. Finally, retailers have an opportunity to set better marketing strategies and understand more consumers intention in store brand food products.